The Effect of Powtoon Interactive Media Based on PjBL to Improve the IPAS Learning Outcomes of Elementary School IV Students - Made Ria Cahyanthi; Ni Nyoman Kurnia Wati; I Made Sedana (Lembaga Bale Literasi, 2026)
The deficient academic performance of fourth-level primary school pupils in Natural and Social Sciences (IPAS) is frequently precipitated by traditional instruction and the utilization of unvarying the process of acquiring knowledge materials. This investigation intends to evaluate and verify the impact of executing interactive Powtoon resources integrated with PjBL on advancing the IPAS academic achievements of fourth-level learners. Employing a quantitative framework via a quasi-experimental approach, specifically utilizing a Posttest-Only Control Group Design, this inquiry embraced a sample pool of 56 schoolchildren gathered through cluster sampling. The intervention group (SDN 5 Dalung, n=28) utilized Powtoon software embedded within the PjBL framework, whereas the comparison group (SDN 2 Dalung, n=28) adhered to a customary instructional framework. Final assessment metrics were examined employing an Independent Samples T-Test subsequently to satisfy the essential preliminary criteria for normality and homogeneity. The outcomes of the hypothesis evaluation revealed a two-tailed significance value of 0.001 (p < 0.05), demonstrating a statistically meaningful disparity in competence. The incorporation of Powtoon as a visual instructional scaffold within the PjBL stages has demonstrated efficiency in making conceptual topics tangible, stimulating inquisitiveness, and amplifying the dynamic engagement of school children in alignment with constructivist tenets. Ultimately, the adoption of PjBL aligned Powtoon interactive multimedia exerts a substantial influence on elevating the science educational achievements of fourth-level learner.